(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
In this paper, we have analyzed the system programming algorithm available in the interpolator device used in CNC systems. Interpolation is a function of the interpolator structure used to process straight lines, circles, and parabolas. The CNC device cannot perform two motions at the same time and feels the need for interpolation when performing a shift along a curved contour relative to any system line on its coordinate axis. Using the Compass 3D program, we created a machine model and included system algorithms that perform interpolation.